The effects of extensive listening on Vietnamese students’ listening skills - Thinh Van Le; Sa Kim Pham (Institut Agama Islam Negeri Palopo, 2020)
University students in Vietnam do not have enough time to practise their listening inside the classroom. Outside the classroom, they do not have chance to practice it. To supplement time constraint in the classroom, extensive listening was employed to assist students to develop their listening skills. The study aims to investigate whether extensive listening ameliorates students’ listening proficiency. Two groups of students from two intact classes: the control group (n = 32) and the experimental group (n = 32) were selected. Before the semester started, all students sat for the pre-listening test. After that, students in the experimental group were advised to listen to fifteen suggested sound files with one file for each week. They were also instructed some listening strategies to self-practise at home while students in the control group did not do any listening tasks at home. After 15 weeks, students in both groups took the post-listening test. The post-interview was conducted to explore how students practiced their listening out of school. The results showed that the experimental group outperformed the control group in the post-test. Some students in the experimental group reported that they practised listening many times and tried to learn as much vocabulary as possible.